Phycoremediation of wastewater for pollutant removal: A green approach to environmental protection and long-term remediation - Dayana Priyadharshini, Stephen; Suresh Babu, Palanisamy; Manikandan, Sivasubramanian; Subbaiya, Ramasamy; Govarthanan, Muthusamy; Karmegam, Natchimuthu (Environmental pollution (1987), 2021)
Surface and water bodies in many parts of the world are affected due to eutrophication, contamination and depletion. The approach of wastewater treatment using algae for eliminating nutrients and other pollutants from domestic wastewater is growing interest among the researchers. However, sustainable treatment of the wastewater is considered to be important in establishing more effective nutrient and pollutant reduction using algal systems. In comparison to the conventional method of remediation, there are opportunities to commercially viable businesses interest with phycoremediation, thus by achieving cost reductions and renewable bioenergy options. Phycoremediation is an intriguing stage for treating wastewater since it provides tertiary bio-treatment while producing potentially valuable biomass that may be used for a variety of applications. Furthermore, the phycoremediation provides the ability to remove heavy metals as well as harmful organic substances, without producing secondary contamination. In this review, the role of microalgae in treating different wastewaters and the process parameters affecting the treatment and future scope of research have been discussed. Though several algae are employed for wastewater treatment, species of the genera Chlamydomonas, Chlorella, and Scenedesmus are extensively utilized. Interestingly, there is a vast scope for employing algal species with high flocculation capacity and adsorption mechanisms for the elimination of microplastics. In addition, the algal biomass generated during phycoremediation has been found to possess high protein and lipid contents, promising their exploitation in biofuel, food and animal feed industries. [Display omitted] •Algal species offer remediation of toxicants in domestic and industrial wastewater.•Phycoremediation effectively removes pollutants along with conventional methods.•Chlorella, Chlamydomonas and Scenedesmus are ideally suited for phycoremediation.•Algal biomass can be used as feedstock for biochar, biofuel, H2 and electricity generation.